The CircRNA-ACAP2/Hsa-miR-21-5p/ Tiam1 Regulatory Feedback Circuit Affects the Proliferation, Migration, and Invasion of Colon Cancer SW480 Cells - He, Jin-Hua; Li, Yu-Guang; Han, Ze-Ping; Zhou, Jia-Bin; Chen, Wei-Ming; Lv, Yu-Bing; He, Meng-Ling; Zuo, Ji-Dong; Zheng, Lei (Cellular physiology and biochemistry, 2018)
Background/Aims: Circular RNAs (circRNAs), a type of RNA that is widely expressed in human cells, have essential roles in the development and progression of cancer. CircRNAs contain microRNA (miRNA) binding sites and can function as miRNA sponges to regulate gene expression by removing the inhibitory effect of an miRNA on its target gene. Methods: We used the bioinformatics software TargetScan and miRanda to predict circRNA-miRNA and miRNAi-Mrna interactions. Rate of inhibiting of proliferation was measured using a WST-8 cell proliferation assay. Clone formation ability was assessed with a clone formation inhibition test. Cell invasion and migration capacity was evaluated by performing a Transwell assay. Relative gene expression was assessed using quantitative real-time polymerase chain reaction and relative protein expression levels were determined with western blotting. circRNA and miRNA interaction was confirmed by dual-luciferase reporter and RNA-pull down assays. Results: In the present study, the miRNA hsa-miR-21-5p was a target of circRNA-ACAP2, and T lymphoma invasion and metastasis protein 1 (Tiam1) was identified as a target gene of hsa-miR-21-5p. CircRNA-ACAP2 and Tiam1 were shown to be highly expressed in colon cancer tissue and colon cancer SW480 cells, but miR-21-5p was expressed at a low level. SW480 cell proliferation was suppressed when the expression of circRNA-ACAP2 and Tiam1 was decreased and the expression of miR-21-5p was increased in vivo and in vitro. SW480 cell migration and invasion were also inhibited under the same circumstance. The circRNA-ACAP2 interaction regulated the expression of miR-21-5p, and miR-21-5p regulated the expression of Tiam1. Down-regulation of circRNA-ACAP2 promoted miR-21-5p expression, which further suppressed the transcription and translation of Tiam1. Conclusion: The present study shows that the circRNA-ACAP2/hsa-miR-21-5p/Tiam1 regulatory feedback circuit could affect the proliferation, migration, and invasion of colon cancer SW480 cells. This was probably due to the fact that circRNA-ACAP2 could act as a miRNA sponge to regulate Tiam1 expression by removing the inhibitory effect of miR-21-5p on Tiam1 expression. The results from this study have revealed new insights into the pathogenicity of colon cancer and may provide novel therapeutic targets for the treatment of colon cancer.